Prevalence and interventions of challenging behavior in children with intellectual disabilities and/or developmental disorders or other disabilities in Iceland - Þórarinn Freyr Grettisson 1988- (2017)
Information on challenging behaviors (CB) of children with intellectual disabilities (ID) and developmental disorders (DD) in Iceland is lacking. However, prevalence of CB in foreign studies ranges from 5% to 28%. Most common interventions for CB are behavioral interventions and medication. Behavioral interventions are effective in reducing CB in children with ID and DD. Although atypical antipsychotics are used to treat CB, they are highly controversial, both because evidence of its effectiveness is lacking and because the use of antipsychotics can lead to severe side effects. The aim of the study was to gather information on prevalence and interventions for CB in children with ID and DD in Iceland. Participants, parents of children with ID, DD, and other disabilities in Iceland, answered a questionnaire that included background questions, a screening question for possible CB, and other questions regarding CB. Data from 205 participants was used to produce results for prevalence. Data from 156 participants was used to produce results for interventions. Children of the majority of participants (76%) had a history of CB, the majority of those children (78%) currently exhibited CB. Parents mostly sought professional assistance from doctors and psychologists. The most prevalent interventions were medicines and visual routine; 29% of those seeking assistance for CB had been prescribed atypical antipsychotics. In the current study, prevalence for CB was higher than reported in foreign studies. Recommended interventions are not in accordance with scientific results. In addition, atypical antipsychotics are being prescribed for populations where effects are minimal and usage is not recommended. Keywords: aggression, attention-deficit/hyperactivity disorder, atypical antipsychotics, autism spectrum disorders, challenging behaviors, developmental disorders, intellectual disabilities, irritability